FISCAL MANAGEMENT OF ENTERPRISE PERSONNEL IN THE CONTEXT OF DEVELOPING INTERNATIONAL ECONOMIC RELATIONS - Bala, Olha; Heletkanych, Volodymyr (Socio-economic relations in the digital society, 2024)
The aim of the study is to characterize the features of fiscal management of enterprise personnel in the context of developing international economic relations. The primary task set within this article is to identify the most optimal practices for implementing fiscal management of enterprise personnel under the increased influence of changes in the international economic environment. It has been determined that the development of international economic relations requires enterprises to adapt their personnel management with consideration of fiscal aspects. Fiscal management of personnel is characterized as a means of optimizing labour costs through the use of tax incentives, subsidies, and other financial instruments, which enhance competitiveness on the international level. It has been established that effective fiscal management ensures that enterprise activities comply with international standards, allowing them to avoid fines and other legal consequences. The role of fiscal management in optimizing the processes of employee relocation between company branches in different countries, ensuring the legality and financial benefit of such relocations, has been characterized. It has been established that proper management of fiscal aspects helps companies expand into new markets by ensuring the effective integration of local and foreign workers into the corporate culture. The necessity of implementing modern technologies and enhancing the qualifications of specialists to improve the fiscal management of personnel has been characterized. It has been proven that effective fiscal management of personnel contributes to optimizing tax obligations, increasing competitiveness, and ensuring the international integration of enterprises.
Keywords: fiscal aspect; fiscal management; personnel management; enterprises; international relations; economic relations